Pola Asuh Autoritatif dan Jenis Kelamin sebagai Prediktor Big Five Personality Factors: Implikasinya Bagi Pelayanan Bimbingan dan Konseling - Dami, Zummy Anselmus; Curniati, Santi (Jurnal Kajian Bimbingan dan Konseling, 2018)
The study aimed to determine the authoritative parenting; gender; gender and the influence of authoritative parenting significantly toward big five personality. This quantitative research with descriptive analysis techniques of Multivariate Analysis of Covariance (MANCOVA) test involved 62 students of eleventh grade of Sekolah Menengah Atas Negeri 2 Kupang as a respondent. Data collection technique used the scale instrument of Parental Authority Questionnaire and the International Personality Item Pool. The results showed that: (1) there was no significant influence of parental authority on the subjects’s big five personality, except extraversion; (2) there was no significant effect of gender on subjects’s big five personality; and (3) there was no significant effect of gender interaction and authoritative parenting on subject’s the big five personality.